A needs analysis of English oral communication skills among tourism management students / Nazirul Mubin Mohd Noor - Nazirul Mubin, Mohd Noor (2019)
This study aims to conduct a needs analysis to examine the oral communication difficulties and needs of final year students of the Diploma in Tourism Management programme in Politeknik Tuanku Syed Sirajuddin, Perlis (PTSS). The study also evaluates the current ESP course, DUE 5012 Communicative English 3 based on feedback obtained from the students and lecturers for the purpose of course improvement in the aspect of English language oral communication. The study explored the English language oral communication difficulties experienced by the students in using English language both in the language classroom and the tourism industry. By using the Needs Analysis framework introduced by Dudley-Evans and St John (1998) that includes Target Situation Analysis (TSA), Present Situation Analysis (PSA) as well as Learning Situation Analysis (LSA), all three research questions in the present study have been answered. A mixed method approach using questionnaire, focus group interviews and face-to-face interviews, was used in the study which involved the participation of 80 students, three EHP lecturers and the Head of the English language Department. Findings indicate that further improvements towards the present EHP course in terms of oral communication sub-skills were required both in speaking and listening skills. Hence, it is highly recommended that the EHP course developer and stakeholders work together to improve the existing EHP courses, specifically in terms of oral communication sub-skills. In addition, improvements were made towards the existing ESP course by incorporating a course which is more learner-centred.